Knowledge Sharing is Knowledge Creation: An Intervention Study of Metaphors for Knowledge - Greve, Linda (Journal of Organizational Knowledge Communication, 2015)
Knowledge sharing and knowledge transfer are important to knowledge communication. However when groups of knowledge workers engage in knowledge communication activities, it easily turns into mere mechanical information processing despite other ambitions. This article relates literature of knowledge communication and knowledge creation to an intervention study in a large Danish food production company. For some time a specific group of employees uttered a wish for knowledge sharing, but it never really happened. The group was observed and submitted to metaphor analysis as well as analysis of co-creation strategies. Confronted with the results, the group completely altered their approach to knowledge sharing and let it become knowledge co-creation. The conclusions are, that knowledge is and can only be a diverse and differentiated concept, and that groups are able to embrace this complexity. Thus rather than reducing complexity and dividing knowledge into to dichotomies or hierarchies, knowledge workers should be enabled to use different strategies for knowledge sharing, -transfer and –creation depending on the task and the nature of the knowledge. However if the ambition is to have a strategy for sharing personal or tacit knowledge, the recommended approach is to co-create new knowledge by use of joint epistemic action.